Sedentary Lifestyle with Social Interaction In Adolescent - Zakiyatul Fuadah, Dina; Siswoaribowo, Andika; Diniaty, Erna (Journal of Applied Nursing and Health, 2021)
Background: Sedentary lifestyle is problematic among millennial generation teenagers. One of the factors is that technological advances in the 4.0 era are very rapid, especially the use of technology such as television, computers, gadgets, and the internet. The purpose of this study was to determine the relationship between Sedentary Lifestyle and Social Interaction in Adolescents at SMP 1 Sudimoro. Methods: The design of this research is the correlation with approach cross-sectional, the sample is 30 respondents, the sampling technique is total sampling. The independent variable in this study is a sedentary lifestyle, while the dependent variable in this study is social interaction. The measuring instrument used is a questionnaire. This study was analyzed using the Spearman Rank Test. Results: The results showed that most (76.7%) experienced a Sedentary Lifestyle in the moderate category, and most (83.3%) social interactions in the maladaptive category. Based on the spearman's rho test, a p-value of 0.033 (α<0.05) was found, meaning that there was a relationship between a sedentary lifestyle and social interaction among adolescents at SMPN 1 Sudimoro. Interaction mediated by screen-based behavior does not teach healthy social skills to adolescents. Conclusion: They are more comfortable and willing to spend more time interacting with their friends in cyberspace. It is recommended for parents to always provide direction and monitoring on the use of media screens in adolescents, as well as reducing a sedentary lifestyle.